2017
DOI: 10.1093/pasj/psx118
|View full text |Cite
|
Sign up to set email alerts
|

J-GEM observations of an electromagnetic counterpart to the neutron star merger GW170817

Abstract: The first detected gravitational wave from a neutron star merger was GW170817. In this study, we present J-GEM follow-up observations of SSS17a, an electromagnetic counterpart of GW170817. SSS17a shows a 2.5-mag decline in the z-band from 1.7 days to 7.7 days after the merger. Such a rapid decline is not comparable with supernovae light curves at any epoch. The color of SSS17a also evolves rapidly and becomes redder for later epochs; the z − H color changed by approximately 2.5 mag in the period of 0.7 days to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
107
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 198 publications
(115 citation statements)
references
References 36 publications
8
107
0
Order By: Relevance
“…Numerical relativity simulations' results, as in figure 8, show clearly that the dynamical ejecta is not spherical; the density in the equatorial region is higher than the density along the polar axis. We know from follow-up observations of GW170817 that the jet opening angle is small (θc ≈ 4 • ; Mooley et al 2018;Troja et al 2018;Ghirlanda et al 2019), this implies that the jet propagated in the polar region of the ejecta. Since the density in the equatorial region is not relevant to jet propagation, and since the scope of this study is limited to jet propagation, we do not include the excess in density in the equatorial region (relative to the polar region) in our calculation for GW170817's jet propagation.…”
Section: Angular Dependence and The Mass Of The Ejecta Mejmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerical relativity simulations' results, as in figure 8, show clearly that the dynamical ejecta is not spherical; the density in the equatorial region is higher than the density along the polar axis. We know from follow-up observations of GW170817 that the jet opening angle is small (θc ≈ 4 • ; Mooley et al 2018;Troja et al 2018;Ghirlanda et al 2019), this implies that the jet propagated in the polar region of the ejecta. Since the density in the equatorial region is not relevant to jet propagation, and since the scope of this study is limited to jet propagation, we do not include the excess in density in the equatorial region (relative to the polar region) in our calculation for GW170817's jet propagation.…”
Section: Angular Dependence and The Mass Of The Ejecta Mejmentioning
confidence: 99%
“…Late afterglow observations of GW170817 provided an estimation of the jet (and cocoon) energy and its final opening angle (Mooley et al 2018;Troja et al 2018;Ghirlanda et al 2019). Radio observations also determined the afterglow's peak time at ∼ 150 days, and the flux at this time.…”
Section: Afterglow Observations: Jet Energy and Opening Anglementioning
confidence: 99%
See 1 more Smart Citation
“…This multimessenger data provided convincing answers to many outstanding questions. For instance, the detection of a short gamma ray burst (GRB) 1.7 seconds after GW170817 [24][25][26], and subsequent kilonova [27][28][29][30][31][36][37][38][39][40][41][42][43][44], confirmed that BNS mergers are a progenitor of these events. Lanthanide signatures in the kilonova light curves also showed BNS mergers to be a major site for nucleosynthesis of elements heavier than iron [40,44,47,48].…”
Section: Introductionmentioning
confidence: 99%
“…As a comparison, the mass of the dynamical ejecta of double NS mergers is typically ∼10 −4 -10 −2 M e (Rosswog 2007;Bauswein et al 2013;Hotokezaka et al 2013a). It also does not conflict with the estimation of M ej ∼10 −3 -10 −2 M e for the dynamical ejecta of GW170817 (Abbott et al 2017d;Utsumi et al 2017;Tanaka et al 2017;Matsumoto et al 2018). In a few recent studies, a more precise ejecta mass of M ej ∼0.05M e was estimated when modeling the GW170817 kilonova (Cowperthwaite et al 2017;Drout et al 2017;Kasliwal et al 2017;Kasen et al 2017;Villar et al 2017;Waxman et al 2017).…”
Section: Numerical Resultsmentioning
confidence: 83%